Karst-specific distribution of endangered Hopea celebica in Bantimurung Bulusaraung National Park, South Sulawesi, Indonesia - NASRI NASRI; KOICHI KAMIYA; TETSUYA SHIMAMURA; TOMOAKI ICHIE (Society for Indonesian Biodiversity, 2025)
Abstract. Nasri, Kamiya K, Shimamura T, Ichie T. 2025. Karst-specific distribution of endangered Hopea celebica in Bantimurung Bulusaraung National Park, Sulawesi. Biodiversitas 26: 5395-5404. Hopea celebica is an endangered tree species endemic to Sulawesi, Indonesia, with limited ecological information available on its habitat preferences. This study aimed to investigate its distribution and habitat association in karst and non-karst areas of Bantimurung Bulusaraung (Babul) National Park, South Sulawesi, Indonesia. Seedlings, saplings, and adult trees were counted in 36 plots (50×20 m) selected using purposive sampling (18 plots in karst and 18 in non-karst areas). Elevation, slope, and canopy cover, were measured in each plot, and soil samples were analyzed for nutrient content and texture. Hopea celebica occurred exclusively in karst areas (12 of 18 plots), particularly in porous and massive karst types, showing a clumped distribution (?²: 36, p<0.001; Morisita’s I?>3, p<0.001). Generalized Linear Model (GLM) and Principal Component Analysis (PCA) showed that H. celebica was positively associated with steeper slope, higher soil pH, and denser canopy, but negatively with elevation. These findings highlighted porous and massive karst areas as key habitats, characterized by well-drained conditions at lower elevation, with healthy regeneration (inverted J-shaped diameter class distribution). This study suggests the need to protect porous and massive karst zones to ensure the long-term survival of H. celebica populations.